Natural logarithm sliding mode control (ln-SMC) using EMRAN for active engine mounting system - Wijaya, Andika Aji; Wahyudi, Martono; Akmeliawati, Rini; Ridhuan Siradj , Fadly Jashi Darsivan (2010)
Robustness of the controller becomes major important factor in active engine mounting system to ensure the vibration of the engine can be attenuated in entire range of operating speed. As robustness is the main advantage of sliding mode control, it has been proposed for vibration control applications. However, most of the proposed sliding mode control are using linear sliding surface. In addition, there is no schematic method to determine the optimum sliding function. In this paper, natural logarithm-based sliding function is introduced. By its nature, natural logarithm function is nonlinear function. Since it consists of one parameter only, which is related to maximum allowable vibration level, it is more easily to be determined by the designer. Moreover, the advantage of fast on-line training using Extended Minimum Resource Allocating Network (EMRAN) algorithm, made it possible to design feedback control law without having to obtain the precise system model which is normally becomes major difficulties of sliding mode approach.